Tradisi Nasi Ambeng sebagai Adat Mendoakan Leluhur dan Menjalin Silaturahmi di Masyarakat Kecamatan Sooko Kabupaten Ponorogo Provinsi Jawa Timur - Tsani, Luthfi Badrus; Ibrahim, Rustam; Syafi’i, Ahmad (MODELING: Jurnal Program Studi PGMI, 2024)
The ruwahan tradition is the tradition of sending prayers to the ancestors independently each family and also together using an Ambengan which is carried out in the mosque. Ambengan is food as a symbol to send prayers and ask God for the safety of the ancestral spirits of the Sooko Ponorogo hamlet community. The people of Sooko Ponorogo Hamlet usually send prayers for a pilgrimage to the grave after the 15th of the month of Syaban. The ruwahan tradition is carried out to send prayers and remind people of their deceased ancestors. This ruwahan tradition has existed for a long time, therefore people now only preserve or continue the tradition. Along with time, the implementation of the ruwahan tradition experienced dynamics by summarizing the tradition. This makes it easier for people to carry out the tradition, but on the other hand there is a cut in the tradition that will reduce the richness of the pre-existing culture.